Patients’ views about treatment with combination therapy for Rheumatoid Arthritis: a comparative qualitative study - Lempp, Heidi (BioMed Central, 2012)
BACKGROUND: Combinations of disease-modifying anti-rheumatic drugs (DMARDs) are increasingly used to control active rheumatoid arthritis (RA); however there is little information about patients’ perspectives, their expectations, concerns and experiences of this intensive treatment. METHOD: We interviewed a quota sample of 18 patients from a single tertiary outpatient clinic, stratified by gender, ethnicity and age, based on the outpatient clinic population. Patients with early RA (<2 years) received combined conventional DMARDs; patients with established RA (>2 years) received combined conventional DMARDs or DMARDs with biologics. RESULTS: Four main themes emerged from the analytical framework: (i) patients’ expectations about the combined treatment focuses mainly on physical symptoms; (ii) the impact of the treatment on quality of life varied with the new medication in both groups (iii) concerns about new interventions concentrated mainly on potential side effects; and (iv) combination therapy can be self-managed in close collaboration with clinic staff, but this requires individualised management approaches. These themes resonate with von Korff’s collaborative management of chronic illness model. CONCLUSION: To our knowledge this is the first qualitative study that examined systematically in patients with early and established RA their expectations, impact on quality of life, concerns about side effects and the management of the treatment when taking combined medication with DMARDs or DMARDs and biologics. Patients have generally positive views of combination DMARDs. Within routine practice settings, achieving medication concordance with complex combined DMARD regimens is challenging, and the concerns vary between patients; careful individual assessments are essential to successfully deliver such intensive treatment.